APRESENTAÇÃO - Emilene Berwig, D.ra Solange; Bronzoni Damascena, D.ra Monique; Michele Pedron Leves, D.ra Aline; Nunes Cavalheiro , D.ra Larissa (Brazilian Journal of Research in Applied Social Sciences, 2024)
APRESENTAÇÃO DO DOSSIÊ